The Kembar Manten in Java Majapahit Wedding Traditions in Mojokerto: Perspectives on Natural Law and Anthropology of Islamic Law - Hidayah, Khoirul; Syarifah, Umaiyatus; Muhammad, Muhammad; Bachri, Syabbul; Roibin, Roibin (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2024)
Majapahit Java has customary law, namely rules prohibiting